ANALISIS YURIDIS TINDAK PIDANA PENGGELAPAN YANG TIMBUL DARI HUBUNGAN SEWA MENYEWA MOBIL DIKAITKAN DENGAN PASAL 372 KUHP - Agustina, Hurip; Suprijatna, Dadang; Hakim, Aal Lukmanul (DERECHTSSTAAT, 2016)
Crime embezzlement car rentals are lately often devastating car rental owner. This is an issue where the meaning of a rule of law if the crime committed community can not be followed by the rule of law, such as crimes by way of evasion is one of the types of crimes against human wealth which is stated in Article 372 of the Criminal Code, which is a crime that does not exist inexhaustible, both from the bottom layer to the top layer of society can also be committing a criminal act embezzlement is a crime that originated from the existence of a trust in others, and that trust is lost because of the lack of an honesty. It is stated that the crime of embezzlement have a problem that is closely linked to attitudes, moral, mental, honesty and trust humans as individuals. The purpose of this study are as follows: 1) To determine and analyze the occurrence of the crime of embezzlement car rental. 2) To know and analyze the application of Article 372 of the Criminal Code the crime of embezzlement in the rental car. 3) To know and analyze the efforts of the police in preventing crime of embezzlement car lease. This study uses normative juridical approach that is used to make the description clear, systematic, transparent and precise about the facts / specific nature of the area and population which is then analyzed to obtain the desired facts. Criminal offense embezzlement rental car can be imprisoned if they meet the overall elements of the offenses charged by the public prosecutor and the offender accountable for his actions. If the offender does not meet one of the elements of which the accused, then it can not be convicted. The elements of criminal responsibility are: 1) committing illegal or criminal acts; 2) for the criminal should be able to be responsible; 3) to have a fault; 4) absence of an excuse. The conclusion from this study is the adoption of Article 372 of the Criminal Code in criminal offenses of embezzlement car rental where the incidence of criminal acts committed tenants for the rented goods belonging to the owner of the rental rights because of misuse or abuse of trust in which the crime of embezzlement are set in the provisions of Article 372 of the Criminal Code.